Photochemical CO2 reduction with mononuclear and dinuclear rhenium catalysts bearing a pendant anthracene chromophore. Issue 7 (4th January 2019) - Liyanage, Nalaka P.; Yang, Weiwei; Guertin, Stephen; Sinha Roy, Sayontani; Carpenter, Casey A.; Adams, Rebecca E.; Schmehl, Russel H.; Delcamp, Jared H.; Jurss, Jonah W.
Abstract : Well-defined dinuclear rhenium photocatalysts featuring an anthracene chromophore are significantly faster and more durable than their mononuclear counterparts. Abstract : A series of anthracene-substituted mononuclear and dinuclear rhenium complexes have been studied for photocatalytic CO2 reduction. The effects on catalytic activity of one versus two covalently-linked active sites, their relative proximity to one another, and the pendant organic chromophore are discussed.